Single-molecule nanopore sensing of actin dynamics and drug binding - Wang,X; Wilkinson,MD; Lin,X; Ren,R; Willison,KR; Ivanov,A; Baum,J; Edel,J (Chemical Science, 2020)
Actin is a key protein in the dynamic processes within the eukaryotic cell. To date, methods exploring the molecular state of actin are limited to insights gained from structural approaches, providing a snapshot of protein folding, or methods that require chemical modifications compromising actin monomer thermostability. Nanopore sensing permits label-free investigation of native proteins and is ideally suited to study proteins such as actin that require specialised buffers and cofactors. Using nanopores, we determined the state of actin at the macromolecular level (filamentous or globular) and in its monomeric form bound to inhibitors. We revealed urea-dependent and voltage-dependent transitional states and observed unfolding process within which sub-populations of transient actin oligomers are visible. We detected, in real-time, filament-growth, and drug-binding at the single-molecule level demonstrating the promise of nanopores sensing for in-depth understanding of protein folding landscapes and for drug discovery.